Modeling of the biliary tree structure in MRCP images - Logeswaran, , Rajasvaran; Eswaran, , Chikkannan (2005)
Magnetic Resonance Cholangio, pancreatography (MRCP) has become a favorite imaging technique for diagnosis of liver diseases, especially those associated with the biliary track. In a typical MRCP examination, a large series of image acquisitions are taken, ranging from the positioning series, to the re-projected image sets of T1- and T2-weighted image series. This paper describes several modeling techniques in 2D and 3D which may aid in highlighting features in the MRCP images, as well as promote some possible compression gains through replacement of certain raw images with the prescribed models.